2016
DOI: 10.11114/aef.v4i1.1921
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating Different Learning Styles in the Teaching of Economics: with Emphasis on Fleming and Mills’s Sensory-based Learning Style Typology

Abstract: Abstract:Students prefer to learn in different ways. These learning preferences are commonly known as learning styles. This variety in learning styles among students suggests that instructors should teach their course materials in different ways to cater to different learning styles. In addition, according to (Nilson 2010), when our society is concerned with fairness and equality, teaching to different styles is a main facet of equity. This paper focuses on Fleming and Mill"s VARK model (1992) to describe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These scholars attribute this to the teaching approaches employed by the teachers, the type of learning material, and the rare engagement of learners in solving mathematical problems in economics, as is the case with imperfect market structures. Moreover, Minarni et al's (2016) assertion is confirmed by Zhang (2017) who also bemoans the lack of content knowledge, lack of adequate resources, and inefficient use of available instructional resources as the reasons for poor academic achievement in economics. Minarni et al (2016) suggest that the teacher should teach the learners in such a way that the learner has an opportunity to solve mathematical problems, as well as to understand mathematical representation in the form of graphs and tables.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…These scholars attribute this to the teaching approaches employed by the teachers, the type of learning material, and the rare engagement of learners in solving mathematical problems in economics, as is the case with imperfect market structures. Moreover, Minarni et al's (2016) assertion is confirmed by Zhang (2017) who also bemoans the lack of content knowledge, lack of adequate resources, and inefficient use of available instructional resources as the reasons for poor academic achievement in economics. Minarni et al (2016) suggest that the teacher should teach the learners in such a way that the learner has an opportunity to solve mathematical problems, as well as to understand mathematical representation in the form of graphs and tables.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 98%
“…The challenge with opportunities to learn with regards to the teaching and learning of imperfect market structures is not a uniquely South African problem. Zhang (2017), for instance, reveals that there are many countries where teachers face challenges related to meaningfully engaging learners. A further review of literature by Minarni et al (2016) shows that there is poor learner achievement in topics that include mathematical concepts in Public Junior High School in Indonesia.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Given the aim of the task at hand which is to classify students according to their learning and thinking styles, independence is important. This, therefore, makes Naïve Bayes preferable over other classification models (Zhang, 2017).…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Principally, this is a suggested teaching tool proposed by him to teach a structured body of economic knowledge that enhance learning in the classroom in terms of comprehension, retention, clarity, big-picture thinking, as well as critical thinking. Zhang (2016) proposes different teaching tools and modes in the teaching of economics which are suitable for accommodating different learning styles classified by Fleming and Mills's sensory-based learning style typology. According to him, -Students prefer to learn in different ways,‖ and this variety suggests that instructors should teach their course materials in different ways so as to cater to different learning styles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Zhang (2016), -economics courses are taught mostly using traditional formats such as lectures along with the presentation of visual instruments such as graphs and charts, which is widely known as the -chalk and talk‖ method,‖ and most of the time, the existence of different cognitive learning outcomes are ignored. This way, the potential improvement in student performance which is achievable from matching instructors' teaching methods with cognitive learning outcomes is lost.…”
Section: Course Formatmentioning
confidence: 99%